A Study of Pharmacognostical Profile of the Herbal Drugs: Exploring the Role of Herbal Drugs in Pharmacotherapy (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The pharmacological therapy of the disease has been carried out using herbs for a considerable period. Plants have from the beginning of time been utilized as medicine. The Rig-veda allusions to the therapeutic qualities of certain herbs seem to be the oldest records of plant usage in medicine in India. Herbal medications were the earliest medicines for humanity, and they continue to play an important part in medicine. The World Health Organization’s statement (WHO), herbal medicine is used by 75-80 percent of the world's population for primary health care due to its cultural acceptance, compatibility with the human body, and lack of adverse effects Crude medicines are plant or animal pharmaceuticals that are made up entirely of natural ingredients that have simply been collected and dried, The phrase natural substances refers to compounds found in nature that have not had their molecular structure altered by humans, and the study which discussed about crude drug, Pharmacology, Plant as Nephroprotective agents, Epidemiology, Pathophysiology, Medicinal chemistry, Evaluation of crude drugs, Drug development process, Drug development